Dampak Implementasi Erp dalam Perbaikan Sistem Distribusi pada PT. Semen Gresik - I Gusti Made Karmawan (Bina Nusantara University, 2013)
This study describes how to implement an ERP system at PT Semen Gresik and compares the positive and negative effects of the implementation in the distribution process improvement. The benefits that can be obtained from this paper is obtaining information of how to implement an ERP system and the positive and negative effects of ERP implementation at PT Semen Gresik in the distribution process improvement. This study was done through documentation review to obtain the description of distribution process in the inventory material planning at PT Semen Gresik. The study resulted in a comparison between the positive and negative aspects as an effect from ERP implementation process at PT Semen Gresik in distribution process improvement. The ERP implementation process at PT Semen Gresik does not only provide more efficiency and effectiveness of distribution system, but also consequences of the impact from the effectiveness and efficiency obtained.